Renewable energy policy in the United Kingdom and in Germany - André Suck (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
The article analyses the development of the national policies in both countries targeted to bringing renewable energy technologies onto the respective electricity market. Commencing with the empirical finding that in the course of the 1990s Germany proved to be more successful than the United Kingdom in establishing renewable energy capacity, it examines the reasons for the different outcomes of this market correction policy. It identifies one main factor, which explains both the different policies and outcomes. This factor is the different political-administrative system - including different modes of sectoral governance of electricity utilities - in combination with different starting points of sectoral liberalisation.Accordingly, the article elaborates the favourable influence of the federal system of government in Germany for the policy-making and implementation of substantial regulations supporting renewable energy generation. Contrary to that, it describes the impediments and restrictions of the unitary political-administrative system of the United Kingdom to realising successful sectoral governance for a greener electricity supply and examines the impacts of early sectoral liberalisation in the United Kingdom - i.e. market creation policies to achieving a competitive and more efficient generation market - for renewable energy policy. As addressed from other prospects in the chapters of the book, it contributes to the discussion of governmental challenges to provide for public services (in this definition including environmental issues) in increasingly competitive markets. It also gives an example for the heterogeneity of regulatory principles that still characterise utility regulation in spite of creating an Internal Energy Market in Europe and strives to give an account for this divergence in utility regulation.
Keywords: 330; Förderung erneuerbarer Energien; Großbritannien; Deutschland